PEMBELAJARAN MENULIS PUISI (STUDI KASUS PADA SISWA KELAS IV SDN 1 KALIKEBO, KECAMATAN TRUCUK, KABUPATEN KLATEN TAHUN PELAJARAN 2025/2026) - Eko Supriyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of poetry writing instruction, identify the challenges encountered during the learning process, and explain the teacher's efforts to overcome these challenges among fourth-grade students at SD Negeri 1 Kalikebo, Trucuk District, Klaten Regency. The study employed a qualitative approach using a case study method. The research participants consisted of the fourth-grade classroom teacher and all 23 fourth-grade students, including 12 boys and 11 girls. Data were collected through classroom observations, interviews, documentation, and field notes. The trustworthiness of the data was ensured through triangulation and member checking, while data analysis followed the interactive model of Miles, Huberman, and Saldaña, which includes data collection, data condensation, data display, and conclusion drawing and verification. The findings revealed that poetry writing instruction was implemented through four stages: prewriting, writing, revising, and appreciation. During the prewriting stage, the teacher utilized the school environment as a source of authentic experiences to help students generate ideas for their poems. In the writing stage, the teacher provided vocabulary support, poetry examples, and individualized guidance to assist students in composing simple poems based on their personal experiences. The revision stage was conducted through small-group discussions to improve word choice, content, and the aesthetic use of language, while the appreciation stage involved students reading their poems aloud in front of the class and displaying their work. The study also identified several challenges, including students' difficulties in generating ideas, limited vocabulary, low self-confidence, and inadequate use of poetic diction, which prevented some students from transforming their experiences into complete and engaging poems. To address these challenges, the teacher employed various strategies, such as providing guiding questions, preparing thematic vocabulary lists, recognizing students' work through appreciation and rewards, and offering individualized assistance throughout the learning process. These efforts were found to enhance students' participation, creativity, and self-confidence in poetry writing activities.